2020
DOI: 10.3390/su12176927
|View full text |Cite
|
Sign up to set email alerts
|

How to Obtain Accurate Environmental Impacts at Early Design Stages in BIM When Using Environmental Product Declaration. A Method to Support Decision-Making

Abstract: The construction sector plays an important role in moving towards a low-carbon economy. Life cycle assessment (LCA) is considered one of the most effective methods of analytically evaluating environmental profiles and an efficient tool for calculating the environmental impacts in building design-oriented methodologies, such as building information modelling (BIM). At early design stages, generic LCA databases are used to conduct the life cycle inventory (LCI), while detailed stages require more detailed data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 29 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…The study published just recently by Palumbo et al shows that, currently, the use of EPD in building information modeling (BIM) is not directly feasible. It requires prior appropriate preparation of information on environmental indicators [63].…”
Section: Discussionmentioning
confidence: 99%
“…The study published just recently by Palumbo et al shows that, currently, the use of EPD in building information modeling (BIM) is not directly feasible. It requires prior appropriate preparation of information on environmental indicators [63].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Švajlenka et al [19] reported the commercial availability of process databases for material and energy flows to improve on the lack of data for LCA. An analysis of state of the art in the integration of LCA with building information modeling (BIM) for data management [20][21][22] highlights many benefits: the integration of BIM-LCA with environmental product declarations (EPDs) for detailed and accurate data for a life cycle inventory [23]; the integration of building LCA and BIM's standard industry foundation classes (IFC) to reduce access barriers and assessment effort/time [24,25]; the comparison of LCAs of buildings with different material structure alternatives [26]. These advantages are the point of departure for assessing the relevance of an exergy-based LCA of buildings.…”
Section: Literature Review: Relevance Of Exergy To a Building Life Cycle Assessmentmentioning
confidence: 99%
“…In particular, the latter authors investigated four different certification systems, assessed the BIM-based workflow usage as input for LCA and provided suggestions for developing building models which were LCA compliant for a smooth and almost automatic certificate production. In the same field, Palumbo et al [17] presented a method for achieving accurate LCA results by integrating Environmental Product Declarations (EPDs) into BIM models at different levels of development (LOD).…”
Section: Introductionmentioning
confidence: 99%